2018
DOI: 10.3329/bpj.v20i2.37883
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Pharmacy Management System and Future Development Approaches in Bangladeshi Hospital

Abstract: The aim of this present work is to find out a suitable and updated hospital pharmacy management system for Bangladesh. Hospital pharmacy is considered as the heart of any hospital because all the departments like surgery, cardiology, nephrology, medicine, pediatric etc. are linked up with pharmacy section. Although the pharmaceutical sector of Bangladesh is enriched so much and the product is up to the mark but the improper management system in hospital pharmacies make the patient’s burden high. So, developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 5 publications
(5 reference statements)
0
20
0
Order By: Relevance
“…Proper knowledge and training are the main back bone of dispensing of drugs as well as the management of drugs. 7 Counseling is also dependent on that. From the survey it was found that, almost 100 % pharmacists who are operating the model pharmacy get the training from Pharmacy Council of Bangladesh (PCB), but it should be conducted at definite time intervals with updated knowledge for better patient management and safety.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proper knowledge and training are the main back bone of dispensing of drugs as well as the management of drugs. 7 Counseling is also dependent on that. From the survey it was found that, almost 100 % pharmacists who are operating the model pharmacy get the training from Pharmacy Council of Bangladesh (PCB), but it should be conducted at definite time intervals with updated knowledge for better patient management and safety.…”
Section: Resultsmentioning
confidence: 99%
“…Greater care should be given during packaging and patients should be well counselled so that they do not take wrong medicine. 7 From table 3 it was found that in about 81% of model pharmacies, there is a separate shelf for prescription and OTC medicine. Prescription drugs are stored with tight security in 70% of the pharmacies.…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacy is taught in about 100 public and private universities in Bangladesh and about 8000 pharmacy students graduate every year [27]. Due to a lack of government policy, hospital, community, and clinical pharmacy in Bangladesh were not well developed [28]. In real Bangladesh pharmacy practice areas for graduate pharmacists in industry i.e.…”
Section: Pharmacy Education In Bangladeshmentioning
confidence: 99%
“…This type of information system is used for managing medications, ABX (antibiotic) prescriptions, and the transfer of medication orders from the physician (who is at the bedside) to the nurse (who is in the medication preparation room) or pharmacist (who is at the pharmacy) [68]. The pharmacist gets the order, approves it, prepares the medicine, and informs the doctor/nurse when the medicine is ready.…”
Section: Iii) Pharmacymentioning
confidence: 99%